Interdependence, Interconnectedness, and Intersectionality: The Ecology of Positive Peace - Amster, Randall (In Factis Pax: Journal of Peace Education and Social Justice, 2025)
one of the foundational links between social and environmental engagement is an overarching sense of interconnectedness.The implications of science, philosophy, spirituality, and lived experience alike are clear on this point: reality is deeply relational, and we are enmeshed in webs of interconnection from the micro to the macro scales in demonstrable ways. Yet despite this, there remains a profound reluctance to recognize interrelatedness. The bifurcation of the world into a zero-sum contest is as much a fiction as is the idea that climate change and environmental destabilization only affect people in some faraway place. Recognizing and remediating this is a central tenet of intersectionality, which understands inequalities and entrenched hierarchies not as immutable characteristics of existence but as system-wide factors reflected within foundational values and structures. This commentary paper brings this emergent lens to bear on socioecological issues from food to climate change, arguing that a systemic approach is necessary for human survival.What is intended with this analysis is not to set about demonstrating or proving that interdependence, interconnectedness, and intersectionality are important perspectives nor that they are empirically valid—instead taking these suppositions as a given and going further to unpack their fuller implications as critical factors for peace and our continued existence. The point is to assert the gravity of the moment as an inflection point in which we have been gifted with an opportunity to bend the “arc of justice” toward its fulfillment. In this work, we are called upon to be engaged actors and not spectators, to ask not merely when but how.